question

Asked by arindeep.singh | 11th Sep, 2020, 01:56: PM

Expert Answer:

Let the original length be x m and breadth by y m.
 
Area = xy m2
 
(x - 5) (y + 3) = xy - 8
 
3x - 5y = 7 ...(1)
 
(x + 3) (y + 2) = xy + 74
 
2x + 3y = 68 ...(2)
 
Multiplying equation (1) with 2 and equation (2) with 3, we get
 
6x - 10y = 14 ...(3)
 
6x + 9y = 204 ...(4)
 
On subtracting (3) from (4), we get, y = 9
 
19x = 218
 
x = 11.47
 
Hence,
 
Length = 11.47 m
 
Breadth = 5.48 m

Answered by Renu Varma | 13th Sep, 2020, 11:13: PM